2018
DOI: 10.3892/ijmm.2018.4021
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin restricts the viability and angiogenesis of vascular endothelial cells by suppressing HIF-1α/ROS/VEGF

Abstract: Angiogenesis is an essential process involved in various physiological, including placentation, and pathological, including cancer and endometriosis, processes. Melatonin (MLT), a well-known natural hormone secreted primarily in the pineal gland, is involved in regulating neoangiogenesis and inhibiting the development of a variety of cancer types, including lung and breast cancer. However, the specific mechanism of its anti-angiogenesis activity has not been systematically elucidated. In the present study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 63 publications
3
84
0
2
Order By: Relevance
“…Interestingly, MSC from both obese and non-obese subjects decreased expression of p16, whereas p21 remained unchanged. In addition, VEGF, an important mediator of the pro-angiogenic function of endothelial cells (Cheng et al, 2019), and its expression falls in injured HUVEC (Wang et al, 2019;Wu et al, 2019), as we observed in our injured HUVEC model. Importantly, HUVEC VEGF gene expression was restored to control levels by co-incubation with MSC from non-obese subjects, whereas MSC from obese subjects failed to reinstate it.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, MSC from both obese and non-obese subjects decreased expression of p16, whereas p21 remained unchanged. In addition, VEGF, an important mediator of the pro-angiogenic function of endothelial cells (Cheng et al, 2019), and its expression falls in injured HUVEC (Wang et al, 2019;Wu et al, 2019), as we observed in our injured HUVEC model. Importantly, HUVEC VEGF gene expression was restored to control levels by co-incubation with MSC from non-obese subjects, whereas MSC from obese subjects failed to reinstate it.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, several pathways related to the degradation of serotonin, dopamine and melatonin, are hypoactive due to a decrease in the expression of two main enzymes, namely aryl sulfotransferase and mono-amine oxidase. This leads to relatively higher levels of these products, specifically in LSECs and to a decrease in angiogenesis [ 39 , 40 ] and a decrease in pro-inflammatory cytokines [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In consideration of the common beneficial action of melatonin and attenuated metabolic processes caused by viral infections, there are reasonable imperatives to propose that this indoleamine may limit symptoms associated with viral infections, including COVID-19. Currently, it is known that severe inflammation induces multiple perturbations, such as enhanced endothelial cell apoptosis or elevation of the production of vascular endothelial growth factor (VEGF), which contributes to edema and the massive release of immune cells, while melatonin is an effective suppressor of VEGF in vascular endothelial cells [60]. Moreover, melatonin was found to be an ameliorating agent against sepsis-induced cardiomyopathy [61,62]; this effect may be also beneficial for some COVID-19 patients in whom an increased risk of sepsis and cardiac arrest accompany severe ALI/ARDS development.…”
Section: Melatonin and Its Adjuvant Effectsmentioning
confidence: 99%